Analysis of Factors Affecting Labour Productivity of Lightweight Masonry - Sartika Meitry; Fepy Supriani; Lindung Zalbuin Mase; Hardiansyah; Rena Misliniyati (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2025)
Labour productivity plays an important role in determining the success of a construction project, especially in lightweight masonry work, which requires high skills and affects not only the aesthetic aspect but also the durability of the building with lightweight materials suitable for high-rise buildings. This study aims to analyse the factors affecting the productivity of lightweight masonry labour on The Establishment of the University of Bengkulu's Hospital Project. The research method used is direct observation in the field, with the work sampling method using the productivity rating approach to calculate the labour utilization rate (LUR) level. The questionnaires were distributed to lightweight masonry workers to identify factors that affect productivity. Data were analysed using validity tests, reliability tests, and the Relative Importance Index (RII) analysis, and relationships between factors were looked for using matrix correlation. The results showed that the average LUR for the level of productivity of lightweight masonry labour was 63.89% which was categorised as productive because it was above 50% with the dominant factor affecting field conditions including the availability of tools, weather, and relationships between workers with an RII value of 0.88 which is included in the high level of importance. The findings contribute to managing labour productivity in construction projects and recommend improving tool management and fostering teamwork in the field.